2002
DOI: 10.1183/09031936.02.00302702
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial effects on twitch transdiaphragmatic pressure

Abstract: Twitch transdiaphragmatic pressure (Pdi,tw), measured following magnetic stimulation of the phrenic nerves, is used to assess diaphragm strength, contractility and fatigue. Although the effects of posture, lung volume and potentiation onPdi,tware well described, it is not known whether the degree of gastric filling affects the measurement.Pdi,twwas recorded in seven healthy volunteers on two occasions with antero-lateral magnetic stimulation of the phrenic nerves. On the first occasion, the subjects had fasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…Despite the expense and bulk of the additional equipment, BAMPS has a significant advantage over CMS and aMS in that it reliably produces a supramaximal Pdi,tw [6,54,55] that is closely similar to values obtained with optimal electrical stimulation. This is probably because BAMPS results in less co-activation of extradiaphragmatic muscles, demonstrated by the similar oesophageal and gastric pressure contributions to Pdi,tw observed with BAMPS and electrical stimulation [54].…”
Section: Unilateral/bilateral Anterolateral Magnetic Phrenic Nerve Stmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite the expense and bulk of the additional equipment, BAMPS has a significant advantage over CMS and aMS in that it reliably produces a supramaximal Pdi,tw [6,54,55] that is closely similar to values obtained with optimal electrical stimulation. This is probably because BAMPS results in less co-activation of extradiaphragmatic muscles, demonstrated by the similar oesophageal and gastric pressure contributions to Pdi,tw observed with BAMPS and electrical stimulation [54].…”
Section: Unilateral/bilateral Anterolateral Magnetic Phrenic Nerve Stmentioning
confidence: 92%
“…However, both abdominal binding and a recent meal increase Pdi,tw [55,63], presumably through a change in abdominal compliance. Studies in intensive care are best performed at least 1-2 h after nasogastric feeding has been stopped, whilst in the outpatient setting, subjects should be studied with the abdomen unbound (e.g.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…This can be established by observing a plateau in the stimulus-response curve. In this study, supramaximality of bilateral anterolateral magnetic phrenic nerve stimulation was not formally assessed in order to limit the number of stimulations administered; however, the authors have previously found the technique to be supramaximal or close to supramaximal [21,28]. The supramaximality of femoral nerve stimulation was formally confirmed in all patients on each occasion.…”
Section: Supramaximalitymentioning
confidence: 99%
“…For the abdominal muscles, force output is estimated by measuring the gastric pressure response to magnetic stimulation of the thoracic nerve roots (61). For nerve stimulation to provide a valid measure of respiratory muscle fatigue it is important to carefully control for several potential sources of error, including supramaximal stimulation (20,128), isovolumic conditions (47,114), abdominal compliance (58,73), and postactivation potentiation (71,143).…”
Section: Exercise-induced Respiratory Muscle Fatiguementioning
confidence: 99%